Virtual exchange program as part of the internationalization of the curriculum strategy in a Mexican context: An ethnographic study - Cuevas Álvarez, María Cruz; Pérez Mendoza, Marcos; Vélez Tellez, Miguel Armando; Zetina Pérez, Carlos David; Coeto Calcáneo, Irma Alejandra; Alfaro García, Sara Margarita (Journal of International Students, 2025)
This paper describes the findings of the information collected during a Virtual Exchange Pilot Program carried out with university students from Greece, Mexico, and Japan as part of the Internationalization of the Curriculum Strategy in a Mexican context. In Mexico, Higher Education Institutions have suffered from budget cuts over the years which has severely impacted on mobility and exchange programs forcing educative administrators to look for alternatives in this matter. This pilot program was carried out during the first semester of 2024. The information was collected with the ethnographic approach and supported the participant observation technique during written, imagery, and videorecorded participations analyzed with free coding. The pilot program has shown that making use of the resources available, internationalization of the curriculum is possible providing students with the opportunity of exposing students with people from other cultures, and to live the experience of interacting with students their own age.